The mechanism of an individual's internal process of work engagement, active learning and adaptive performance - Widya Nandini; Aurik Gustomo; Dedy Sushandoyo (Economies, 2022)
This paper aims to investigate the mechanism linking an individual's internal processes, work engagement, active learning, and adaptive performance in three of Indonesia's digital technology-based companies. The research uses a mixed-method approach. The first study used a quantitative research method in which the data is based on a survey of 185 employees and the collected survey data is then analyzed using the Structural Equation Modeling technique. The second study used a qualitative research method where the data is gathered from 17 managers through semi-structured interviews. We found from the quantitative research that work engagement fully mediates the relationship between self-efficacy and a growth mindset toward active learning. Meanwhile, a partial mediating effect of active learning between work engagement and adaptive performance was also discovered. Based on our literature study, previous research has shown inconsistent findings on the relationship between growth mindset and work engagement. Our findings contribute to the existing literature by clarifying the direct relationship between growth mindset and work engagement. Meanwhile, the qualitative findings emphasized that there are two mechanisms underlies individual adaptive performance (i.e., work engagement and active learning). Additionally, the active learning process promotes continuous new knowledge accumulation to produce new innovation inside an organization.
Keywords: 330; active learning; adaptive performance; engagement of employees; growth mindset; innovation management; self-efficacy